The impact of COVID‐19 on the well‐being and cognition of older adults living in the United States and Latin America. (31st December 2021) - Babulal, Ganesh M; Torres, Valeria L; Acosta, Daisy M; Aguero, Cinthya; Aguilar‐Navarro, Sara Gloria; Amariglio, Rebecca E; Ussui, Juliana Aya; Baena, Ana Y; Bocanegra, Yamile; Brucki, Sonia MD; Bustin, Julian; Cabrera, Diego; et al.
Abstract: Background: In the COVID‐19 pandemic, older adults from vulnerable ethnoracial groups are at high risk of infection, hospitalization, and death. We aimed to explore the pandemic's impact on the well‐being and cognition of older adults within and outside of the United States (US). Method: 1, 747 (646 White, 991 Latino, 77 Black, 33 Asian; 72% female) individuals from the US and 14 Latin American countries completed an online survey regarding well‐being and cognition during the pandemic. Outcome variables (pandemic impact, discrimination, loneliness, purpose of life, subjective cognitive concerns) were compared across four US ethnoracial groups, and Latinos living in the US and Latin America. Result: Mean age was 66·5 ( SD = 7·70) years and mean education was 15·4 ( SD = 2·76) years. We found no differences in the pandemic's overall impact across US ethnoracial groups. Compared to Whites, Latinos reported greater economic impact ( p < ·001, ηp 2 = .031); while Blacks reported experiencing discrimination more often ( p < ·001, ηp 2 = .050). Blacks and Latinos reported more positive coping ( p < ·001, ηp 2 = 040). Latin American Latinos reported greater pandemic impact ( p < ·001, ηp 2 =.013 ), more positive coping ( p =·006, ηp 2 =.008 ), and less discrimination than US Latinos ( p < ·001, ηp 2 = .013 ). Conclusion: The COVID‐19 pandemic has differentially impacted the well‐being of older ethnically diverse individuals in the US and Latin America. Future studies should examine how mediators like income and coping skills modify the pandemic's impact.